Asymmetric responses to multidimensional performance evaluation systems: The role of non-pathological narcissism. (December 2022) - Dworkis, Kelsey Kay; Patelli, Lorenzo
Abstract: We experimentally investigate how narcissism affects individuals' responses to multidimensional performance evaluation systems (PES). Because these systems are characterized by cognitive conflict, which inhibits performance, prior research has explored how exogenous control systems, such as the provision of feedback, can enhance task performance. Our experimental evidence shows that narcissism moderates the performance implications of conflict and of the tone with which feedback is provided under multidimensional PES. In Experiment 1, we find that task performance among participants with a low (high) level of narcissism is (not) significantly worse under PES associated with higher conflict. In Experiment 2, we find that, while task performance of all participants is better (worse) when feedback is provided with encouraging (discouraging) tone, the effects are stronger among participants with a high level of narcissism. Collectively, our findings suggest that under multidimensional PES, task performance among narcissists is less susceptible to conflict consistent with their analytic cognitive-perceptual style and abnormal need for self-enhancement, and more susceptible to feedback tone, consistent with their grandiose self-image. Hence, we inform both research and practice on the effectiveness of multidimensional PES by examining the role of personality.